First record of Astathelohania contejeani (Henneguy, 1892) in the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) from Belarus - Śliwińska Karolina; Skuratovich Elena; Alekhnovich Anatoly (Oceanological and Hydrobiological Studies)
Porcelain disease, caused by the parasite Astathelohania contejeani, is a fatal disease for freshwater crayfish. Previously published data provide information on the occurrence of A. contejeani in various crayfish species. However, its prevalence in host populations remains largely undetermined. This issue is relevant to the narrow-clawed crayfish Pontastacus leptodactylus, a species of high commercial value in Eastern Europe. A single published report addressed a potential microsporidia infection in P. leptodactylus, but without specific data on geographical location and prevalence. We present the first detailed information on the prevalence of A. contejeani in the P. leptodactylus population from Lake Losvido, including an assessment of the infection rate through both visual and molecular assessment. Astathelohania contejeani was observed in 1.56% of 128 crayfish examined visually. Of the 37 asymptomatic crayfish samples analyzed, 29.7% were found to be carriers. This finding suggests that parasitism of A. contejeani occurs frequently in the P. leptodactylus population in Lake Losvido prior to the manifestation of observable disease symptoms.